A history of law in Canada. Volume 1, Beginnings to 1866 - Girard, Philip; Phillips, Jim, 1954-; Brown, R. Blake (Toronto ; Buffalo ; London : published for The Osgoode Society for Canadian Legal History by University of Toronto Press, 2018)
"A History of Law in Canada is an important three-volume project. Volume One begins at a time just prior to European contact and continues to the 1860s, Volume Two covers the half century after Confederation, and Volume Three covers the period from the beginning of the First World War to 1982, with a postscript taking the account to approximately 2000. The history of law includes substantive law, legal institutions, legal actors, and legal culture. The authors assume that since 1500 there have been three legal systems in Canada -- the Indigenous, the French, and the English. At all times, these systems have co-existed and interacted, with the relative power and influence of each being more or less dominant in different periods. The history of law cannot be treated in isolation, and this book examines law as a dynamic process, shaped by and affecting other histories over the long term. The law guided and was guided by economic developments, was influenced and moulded by the nature and trajectory of political ideas and institutions, and variously exacerbated or mediated intercultural exchange and conflict. These themes are apparent in this examination, and through most areas of law including land settlement and tenure, and family, commercial, constitutional, and criminal law"--
PART FOUR: BRITISH NORTH AMERICA, 1815-1860s. 21. Law in British North America, 1815-1866: Introduction -- 22. Court Systems and Judicial Personnel -- 23. Sources of Law and Law ReformSources of Law in Common Law Jurisdictions -- 24. Indigenous Law in British North America -- 25. The Legal Professions -- 26. Constitutional Developments I: European-Indigenous Relations, the Old Colonial System, and the Rebellions, 1815-ca 1839 -- 27. Constitutional Developments II: The Act of Union, Responsible Government, and the Origins of Acculturation Policy, ca 1840-1866T -- 28. Criminal Justice I: Criminal Law, Punishment, and Policing -- 29. Criminal Justice II: The Criminal Trial -- 30. Land Law and Policy: Titles, Tenure, Squatters, Indigenous Dispossession, and the Rights and Obligations of Ownership -- 31. Law and the Economy I: Common Law, Statutes, and the Emergence of the CorporationJudges, Private Law, and the Economy -- 32. Law and the Economy II: Debtor-Creditor Law -- 33. Less Favoured by Law I: Blacks and Workers -- 34. Less Favoured by Law II: Women and the Law -- 35. Law and Legal Institutions on the Eve of Confederation: The British North American Legacy.
Includes bibliographical references and index.
Philip Girard is a professor of law at Osgoode Hall Law School at York University. Jim Phillips is a professor in the Faculty of Law and the Department of History at the University of Toronto. R. Blake Brown is a professor of history at Saint Mary's University.
Print version record.
JSTOR
Keywords: Law -- Canada -- History; Droit -- Canada -- Histoire; LAW -- Essays; LAW -- General Practice; LAW -- Jurisprudence; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; LAW -- Reference; HISTORY -- Canada -- Pre-Confederation (to 1867); Law; Canada; Electronic books; History